Keep it Simple! German Voters' Limited Competence to Evaluate Electoral Systems' Functions. Issue 4 (2nd October 2022) - Jankowski, Michael; Linhart, Eric; Tepe, Markus
Abstract : Electoral systems are a fundamental feature of any democratic system, and the design of an electoral system can have a tremendous impact on party-, candidate-, and voter-behaviour. However, in order to use all features of an electoral system as intended, voters must have a clear understanding of how their electoral system actually works. While earlier studies have already shown that many German voters have limited knowledge about the characteristics of their electoral systems, we shift the focus to the more fundamental understanding of electoral systems' objectives. Therefore, this paper addresses the question of how competent voters are in understanding and applying six core functions of electoral systems: (1) proportionality, (2) minority representation, (3) party system concentration, (4) personalisation, (5) legitimacy, and (6) comprehensibility. Based on an original representative survey of German citizens, we demonstrate that only a minority of the electorate is competent enough to capture these functions. We further demonstrate how education and political interest influence voters' understanding of electoral systems. While the political logic of compromises in electoral reforms tends to create electoral systems of growing complexity, our findings strongly suggest policymakers must bear in mind voters' limited resources and capabilities to fully understand electoral systems' functions.